Uterine perforation in a 27-year-old woman, a rare complication of copper intra-uterine device: a case report - Amponsah-Tabi, Seth; Kekertsor, Martin Y.; A. Ofori, Helen; Bosque-Hamilton, Cecil Y. A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Uterine perforation by copper intra-uterine device (IUD) though rare presents as a management challenge to the clinician. A 27-year-old woman of African descent presented with missing strings of a copper IUD that was inserted 2 weeks ago. Ultrasonography (USG) showed device outside the uterus. The initially planned laparoscopic removal at a teaching hospital was unsuccessful due to diagnostic challenges. Copper IUD was successfully removed by laparotomy under USG guidance. Copper IUD is a safe and effective method of contraception. Uterine perforation is a rare complication. Early identification, counselling and prompt removal are necessary to avert further complications.